2019
DOI: 10.1021/acsomega.9b00583
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Biobutanol Production in Folic Acid-Induced Medium by Using Clostridium acetobutylicum NRRL B-527

Abstract: The conventional acetone–butanol–ethanol fermentation process suffers from several key hurdles viz. low solvent titer, insufficient yield and productivity, and solvent intolerance which largely affect butanol commercialization. To counteract these issues, the effect of stimulator, namely, folic acid was investigated in the present study to improve butanol titer. Folic acid is involved in biosynthesis of a diverse range of cellular components, which subsequently alter the amino acid balance. Therefore, differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
(67 reference statements)
0
6
0
Order By: Relevance
“…Acids, various metals and minerals, vitamins, and amino acids also affect both solvent production and sporulation in clostridia (List et al 2019;Mukherjee et al 2019;Nimbalkar et al 2018Nimbalkar et al , 2019Reeve and Reid 2016), but few studies mentioned their impact on sporulation. Long et al (1984a) investigated butyrate and acetate's effect on sporulation in C. saccharobutylicum by adding them to the medium at the start of the fermentation in different concentrations.…”
Section: Other Media Componentsmentioning
confidence: 99%
“…Acids, various metals and minerals, vitamins, and amino acids also affect both solvent production and sporulation in clostridia (List et al 2019;Mukherjee et al 2019;Nimbalkar et al 2018Nimbalkar et al , 2019Reeve and Reid 2016), but few studies mentioned their impact on sporulation. Long et al (1984a) investigated butyrate and acetate's effect on sporulation in C. saccharobutylicum by adding them to the medium at the start of the fermentation in different concentrations.…”
Section: Other Media Componentsmentioning
confidence: 99%
“…It has been reported that the supplementation of micronutrients/cofactors at low concentrations could maintain high ORP (oxidoreduction potential) levels, which is directly attributed to the earlier initiation of solventogenesis with improved butanol titer . Moreover, several research studies also pointed out that a higher concentration of metabolic precursors is detrimental to clostridial butanol production. , Hence, soy meal addition was not continued beyond 5 g L –1 in the present study. Nevertheless, around a threefold increment in butanol titer was achieved as compared to control (without soy meal).…”
Section: Resultsmentioning
confidence: 78%
“…40 Moreover, several research studies also pointed out that a higher concentration of metabolic precursors is detrimental to clostridial butanol production. 41,42 Hence, soy meal addition was not continued beyond 5 g L −1 in the present study. Nevertheless, around a threefold increment in butanol titer was achieved as compared to control (without soy meal).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It is produced as a “natural” fuel via the fermentation of potatoes, sugar cane, sugar beet, corn, cassava, sorghum, wheat and cellulose, with the use of the bacterium Clostridia acetobutilicum [ 78 ]. Applying Escherichia coli as a fermentation agent is much less effective in terms of the yield of biobutanol [ 79 ]. Another advantage over bioethanol is the ability of Clostridia acetobutilicum to transform biomass that contains polymeric cellulose [ 80 ].…”
Section: Conditionally Renewable Alternative Sources Of Energymentioning
confidence: 99%